CHATBOT PARA BIBLIOTECAS: Um assistente virtual para tirar dúvidas relacionadas à Lei de Direito Autoral - SANTOS, Gracelynne Oliveira (2023)
Law 9.610/98, related to copyright in Brazil, is extensive and, throughout its 115 articles, protects literary, scientific, artistic and musical intellectual works, externalized by any means. Libraries, through their social role of democratizing and disseminating information to the community they serve, make available different works protected by the Copyright Law, but they do not have the control to check whether users infringe this Law when using borrowed informational materials. The objective of this work is to offer a technological solution to help users to solve doubts related to copyright issues. Thus, a chatbot will be developed that will answer questions based on the Copyright Law. This computer program corresponds to a demand from the libraries of the Federal University of Maranhão (UFMA) and will be available on the official page of the Integrated Directorate of Libraries (DIB). Applied research with a qualitative approach was adopted in the methodology of this work and, as for the objectives, it will be of a prescriptive exploratory nature. For a better deepening of the research related to this work, the history of libraries, copyrights and the chatbot was outlined, because only then would it be possible to understand the relevance of presenting a computer program that would allow the deepening of this Law. A prospective study was carried out with the objective of identifying computer programs that were similar to the chatbot proposed in this research. 139 certificates of computer programs were retrieved from the National Institute of Industrial Property (INPI) database. The programs were classified according to the Field of Application, Type of Program and Category tables. The technological tool Capterra was also used to search for prior art. Through this tool, 119 computer programs were retrieved, classified according to the “resource” filter. After analyzing the information retrieved from the INPI computer program base and the Capterra technological tool, no computer programs that had similarity with the chatbot related to the Copyright Law were identified.